PENGARUH PEMBELAJARAN MEDIA KAHOOT TERHADAP KREATIVITAS BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS VIII MTS PERGURUAN MU’ALLIMAT CUKIR JOMBANG - Mahbubah , Royyanatul; Arifin Hasan, Zaenal; jumari (EL-Islam, 2023)
Abstract: Presenting interactive quizzes by utilizing educational platforms such as Kahoot is a way to make learning activities fun and encourage students' interest in learning. The use of Kahoot media in learning can foster interactive and creativity and engagement during the learning process by answering questions and participating in quizzes. The purpose of this study is to determine Kahoot media learning, learning creativity and determine the influence of Kahoot media learning on student learning creativity in class VIII Islamic Cultural History subjects at MTs Perguruan Mu'allimat Cukir Jombang. This study used a quantitative approach and a type of Quasi-experimental Design research, used to determine the scores of students from classes that were given treatment (experiments), and classes that were not treated (control) in improvement. Desain penelitian Pretest-Posttest Control Group Design. The results of this study are: 1) The application of Kahoot Media learning in the subject of Islamic Cultural History is very satisfactory there is a significant increase before and after learning with Kahot media. It can be seen from the average pretest score of 40.33 and the post test score of 85.33. 2) Student learning creativity using Kahoot media and other than Kahoot media there are differences in results, in the experimental class the average pretest score was 40.33 and post test 85.33 while in the control class the average pretest score was 48.00 and post test 53.00, in the experimental class there was a significant increase in creativity while in the control class the increase was only 23.3%. 3) Based on the Paired Sample T-Test test, there is an influence of Kahoot media learning on student learning creativity in class VIII Islamic Cultural History subjects at MTs Perguruan Mu'allimat Cukir Jombang with a sig (2-tailed) value of 0.000 < 0.05, then H0 is rejected and HA accepted.